Cerebrospinal Fluid Presepsin As a Marker of Nosocomial Infections of the Central Nervous System: A Prospective Observational Study - Abudeev, Sergey A.; Kiselev, Kirill V.; Kruglyakov, Nikolay M.; Belousova, Ksenia A.; Lobanova, Inna N.; Parinov, Oleg V.; Udalov, Yuriy D.; Zabelin, Maxim A.; Samoilov, Alexandr S.; Cesnulis, Evaldas; Killeen, Tim; Popugaev, Konstantin A. (Frontiers in Neurology, 2018)
Background Nosocomial CNS infection (NI-CNS) is a common and serious complication in neurocritical care patients. Timely, accurate diagnosis of NI-CNS is crucial, yet current infection markers lack specificity and/or sensitivity. Presepsin (PSP) is a novel biomarker of macrophage activation. Its utility in NI-CNS has not been explored. We first determined the normal range of cerebrospinal fluid (CSF) PSP in a control group without brain injury before collecting data on CSF PSP levels in neurocritical care patients. Samples were analyzed in four groups defined by systemic and neurological infection status. Results CSF PSP levels in 15 control patients without neurological injury were 50–100 pg/ml. Ninety-seven CSF samples were collected from 21 neurocritical care patients. In patients without NI-CNS or systemic infection, CSF PSP was 340.4 ± 201.1 pg/ml. Isolated NI-CNS was associated with CSF PSP levels of 640.8 ± 235.5 pg/ml, while levels in systemic infection without NI-CNS were 580.1 ± 329.7 pg/ml. Patients with both NI-CNS and systemic infection had CSF PSP levels of 1,047.7 ± 166.2 pg/ml. In neurocritical care patients without systemic infection, a cut-off value of 321 pg/ml gives sensitivity and specificity for NI-CNS of 100 and 58.3%, respectively. Conclusion CSF PSP may prove useful in diagnosing NI-CNS, but its current utility is as an additional marker only.